1995
DOI: 10.1021/jf00056a046
|View full text |Cite
|
Sign up to set email alerts
|

Volatile Chemicals Formed in the Headspace of a Heated D-Glucose/L-Cysteine Maillard Model System

Abstract: Volatile chemicals formed from heated D-glucose, L-cysteine, or D-glucose/L-cysteine were collected in three traps (20, 0, and -78 "C) connected in series, recovered, and analyzed. A total of 130 chemicals was positively identified: 41 identified in the samples from D-glUCOSe heated alone, 52 in the samples from L-cysteine heated alone, and 93 in the samples from L-cysteine/D-glucose heated together. The heterocyclic compounds identified were 16 thiophenes, 16 furans, 11 pyridines, 10 pyrazines, 9 thiazoles, 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 19 publications
1
47
0
Order By: Relevance
“…Numerous sulphur containing heterocycles were formed from the precursors (93 compounds were identified in a heated cysteine-glucose mixture), which would otherwise react to form pyrazines [32]. Our results were similar to those reported in extruded wheat flour containing the added cysteine [33,34].…”
Section: Composition Of the Pyrazine Fractionsupporting
confidence: 88%
“…Numerous sulphur containing heterocycles were formed from the precursors (93 compounds were identified in a heated cysteine-glucose mixture), which would otherwise react to form pyrazines [32]. Our results were similar to those reported in extruded wheat flour containing the added cysteine [33,34].…”
Section: Composition Of the Pyrazine Fractionsupporting
confidence: 88%
“…Dry heating of L-cysteine systems seems to favour the formation of thiazolines. Umano et al (1995) observed 2-methylthiazolidine as the major volatile in a dry-heated L-cysteine/glucose mixture, although this most probably has only a minor impact on the flavour. Possibly it is formed via a reaction of the intermediate acetaldehyde with cysteamine originating from L-cysteine decarboxylation.…”
Section: The Maillard Reaction Of Cysteinementioning
confidence: 94%
“…Acetaldehyde derived from cysteine in the Maillard reaction (Vernin and Metzger 1981; Vernin and others 1992; Perez Locas and Yaylayan 2004) has been postulated as the source of the C(2) fragment in the thermal degradation of cysteine alone (Shu and others 1985). Cysteine alone at 180 °C for 2 h gave mostly 2‐methylthiazolidine and measurable amounts of 2‐ethylthiazolidine, 2‐methylthiazole, 2‐ethylthiazole, 2‐methyl‐2‐thiazoline among other heterocyclic products (Umano and others 1995). In another thermal study, cysteine alone gave 2‐methylthiazole, 2‐methyl‐2‐thiazoline, and 2‐methylthiazolidine.…”
Section: Introductionmentioning
confidence: 99%